Comparison of Meat Quality From Hanwoo Cattle Having Yellow and White Carcass Fat - Hye-Jin Kim; Seungchul Lee; Sethukali, A.; Hoe-Yong Jung; Hak-Pil Kim; Juae Gil; Chang Wan Sun; Cheorun Jo (Iowa State University Digital Press, 2023)
This study aimed to investigate the relationship between the normal and yellow- colored fat on carcass on carotenoid contents in fat and meat quality of Hanwoo beef. A total of 20 female cattle, comprising 10 with normal carcass fat color (normal group) and 10 with yellow carcass fat color (yellow group), were collected from slaughterhouses throughout the country in Korea from May to July 2022. The color, fatty acid composition, and carotenoid contents in carcass fat, as well as various parameters related to meat quality such as proximate composition, pH, color, cooking loss, shear force, and thiobarbituric acid reactive substances in the striploin were measured. The results indicated that the yellowness of carcass fat was primarily influenced by the carotenoid content in the fat (r=0.540, P<0.05) and was not affected by other carcass properties such as quality grade, maturity, and age. The yellow group showed distinct differences in yellowness and fatty acid composition of the carcass fat compared to the normal group, with lower levels of saturated fatty acids and higher levels of monounsaturated fatty acids (P<0.05). However, no significant differences were observed in the meat quality parameters between the normal and yellow groups, suggesting that the yellowness of carcass fat did not significantly correlate with the inferior physicochemical properties of Hanwoo beef. Although further research is needed to better understand the complex factors contributing to the appearance of yellow carcass fat in Korea, this study highlights that beef having yellow carcass fat does not necessarily have a negative effect on meat quality.
Keywords: Yellow fat; Carotenoid; Quality grade; Fat color; Fatty acids